Design of a preorganized adsorbent for the removal of chromate from wastewater under neutral conditions. Issue 24 (4th March 2019) - Jin, Limin; Sun, Guoxin; Zhang, Hao; Yuan, Guangzheng; Ma, Jiapeng; Peng, Xiujing; Cui, Yu
Abstract : A preorganized structure with two positive nitrogen ions linked by a carbon atom was designed. This structure acts like crab pincers to tightly entrap chromate. Abstract : A preorganized structure with two positive nitrogen ions linked by a carbon atom was designed. This structure acts like crab pincers to tightly entrap chromate. The adsorbent based on the designed structure incorporated into graphene oxide (PS-GO) has a dramatically enhanced binding affinity to Cr(vi ) under neutral conditions.